2019
DOI: 10.3390/molecules24234400
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Use of Stimulatory Agents to Enhance the Production and Hypoglycaemic Activity of Polysaccharides from Inonotus obliquus by Submerged Fermentation

Abstract: This study aimed to determine the effect of applying stimulatory agents to liquid cultured Inonotus obliquus on the simultaneous accumulation of exo-polysaccharides (EPS) and their monosaccharide composition. Different stimulatory agents (VB6, VB1, betulin and birch extract) were investigated for their effects on active exo-polysaccharides by submerged fermentation of I. obliquus. The mycelial biomass, reducing sugar content, EPS yield and α-glucosidase inhibition rate were determined, and the EPS obtained was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Among all the active components in Inonotus obliquus , Inonotus obliquus polysaccharides have the broadest biological activity, such as anticancer, hypoglycemic, anti-inflammatory, and anti-oxidation effects [ 8 , 22 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Through the number of Scopus-indexed publication numbers (archived until 15 March 2021) for polysaccharide bioactivity, Inonotus obliquus , Inonotus obliquus polysaccharide related articles, a certain degree of upward trend can be seen ( Figure 1 ), which means that the medicinal value and health value of Inonotus obliquus have been widely recognized and affirmed [ 5 , 6 , 62 , 63 , 64 ], making it worthwhile to review Inonotus obliquus polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“…Among all the active components in Inonotus obliquus , Inonotus obliquus polysaccharides have the broadest biological activity, such as anticancer, hypoglycemic, anti-inflammatory, and anti-oxidation effects [ 8 , 22 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Through the number of Scopus-indexed publication numbers (archived until 15 March 2021) for polysaccharide bioactivity, Inonotus obliquus , Inonotus obliquus polysaccharide related articles, a certain degree of upward trend can be seen ( Figure 1 ), which means that the medicinal value and health value of Inonotus obliquus have been widely recognized and affirmed [ 5 , 6 , 62 , 63 , 64 ], making it worthwhile to review Inonotus obliquus polysaccharides.…”
Section: Introductionmentioning
confidence: 99%
“… 114 To date, it has been shown that I. obliquus polysaccharides have hypoglycemic activity. 115 , 116 Unfortunately, the exact mechanism of action has not been elucidated. It has been described that I. obliquus polysaccharides in streptozotocin (STZ)-induced diabetic Wistar rats reduced blood glucose levels and restored the structure of β-cells after diabetes-induced cellular damage.…”
Section: Biological Properties Of Inonotus Obliquus Extractsmentioning
confidence: 99%
“…Besides, cultivating the mycelium with the aqueous extracts or methanolic extracts of birch bark, birch core or chitosan could significantly enhance the steroid production of inotodiol, ergosterol peroxide, betulin, ergosterol, cholesterol, lanosterol, stigmasterol, and sitosterol (Kahlos, 1994;Wang et al, 2014). Similarly, the addition of betulin, or various spent substrates such as bark residues of white birch, birch extracts, corn grain and mulberry powder in the medium, or exposing into light at certain wavelengthes to mimic the wild nutritional or host condition could efficiently stimulate the growth of chaga mycelium as well as its polysaccharide yield (Chen et al, 2020b;Fradj et al, 2019;Poyedinok et al, 2015;Wang et al, 2019). Other stimulants such as colloidal metal nanoparticles, AgNPs (silver nanonparticles), could inhibit polysaccharide and flavonoid synthesis but may stimulate melanin synthesis while MgNPs (magnesium nanonparticles) colloid was effective in stimulating the accumulation of endopolysaccharides, flavonoids, and melanin pigments (Poyedinok et al, 2020).…”
Section: Terpenoidsmentioning
confidence: 99%